Объяснение:
Na₂SО₃+Ca(OH)₂=CaSО₃↓+2NaOH
2Na⁺ + SO₃²⁻ + Ca²⁺ + 2OH⁻ = CaSО₃↓+2Na⁺ + OH⁻
Ca²⁺ + SO₃²⁻ = CaSO₃↓
Полное: 2Na(+) + SO3(2-) + Ca(2+) + 2OH(-) = CaSO3(стрелочка вниз) + 2Na(+) + 2OH(-)
Краткое: SO3(2-) + Ca(2+) = CaSO3(стрелочка вниз)
все числа с плюсами и минусами, написанные рядом с ионами в скобках, надо написать сверху справа от них
Объяснение:
Na₂SО₃+Ca(OH)₂=CaSО₃↓+2NaOH
2Na⁺ + SO₃²⁻ + Ca²⁺ + 2OH⁻ = CaSО₃↓+2Na⁺ + OH⁻
Ca²⁺ + SO₃²⁻ = CaSO₃↓
Полное: 2Na(+) + SO3(2-) + Ca(2+) + 2OH(-) = CaSO3(стрелочка вниз) + 2Na(+) + 2OH(-)
Краткое: SO3(2-) + Ca(2+) = CaSO3(стрелочка вниз)
Объяснение:
все числа с плюсами и минусами, написанные рядом с ионами в скобках, надо написать сверху справа от них